DIAGNOSIS AND TREATMENT OF OSSIFICATION OF THE POSTERIOR LONGITUDINAL LINATION OF THE SPINE. - Khudaiberdiev K.T; Jalilov F.R; Isakov B.M.; Botirov N.T.; Mamadjanov K.Kh. (Scholar Express Journals, 2022)
The vast majority of vertebrogenic diseases of the nervous system are associated with dystrophic lesions of the spine. Traditionally, all various dystrophic processes are denoted by the term "osteochondrosis" (in the English literature - "spondylosis"). This approach has developed historically and is associated with a large experience gained as a result of the surgical treatment of herniated discs of the spine. Currently, the clinic of discogenic radicular syndromes is well known, they study biochemical disorders in the discs in the process of their dystrophy and the resulting immunological changes.
Keywords: osteochondrosis; ossifying ligamentosis; identify specific clinical radiological syndromes